Analisis Yuridis Normatif Pengasuhan Anak pada Pasangan Tunagrahita Perspektif Maqasid Al-Syariah dan Undang-Undang Perlindungan Anak Nomor 35 Tahun 2014 - Andri Yurinta (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2026)
This study examines the patterns and implications of child custody (hadhanah) practiced by intellectually disabled (tunagrahita) couples in Carangrejo Village, Ponorogo Regency, East Java, Indonesia. Employing a socio-legal qualitative field research design with purposive sampling, data were collected from three couples with intellectual disabilities through in-depth semi-structured interviews, participant observation, and document analysis (October 2023), triangulated with extended family members, neighbors, and local religious authorities. The theoretical framework integrates: (a) comparative hadhanah jurisprudence across the four major Sunni madhahib (Hanafi, Maliki, Shafi'i, Hanbali), with focus on ahliyyah al-ada' (legal capacity) and the conditions of the hadhinah (female custodian); (b) the maqasid al-shari'ah framework, specifically hifzh al-nasl (preservation of progeny) as elaborated by Al-Syatibi and Ibn 'Ashur; and (c) Indonesian Child Protection Law No. 35 of 2014, the Compilation of Islamic Law (KHI), and the UN Convention on the Rights of the Child (UNCRC) 1989. Findings reveal that all three couples adopt a permissive-indulgent parenting style as a structural consequence of their cognitive limitations, not a conscious choice. The quality of social support networks emerges as the strongest determinant of child developmental outcomes. From the hadhanah perspective, intellectual disability does not constitute absolute grounds for forfeiture of custody; rather, it necessitates a graduated ahliyyah assessment. This study proposes a maslahah-oriented Model Hadhanah Inklusif Berbasis Maslahah (MHIBM) comprising multidisciplinary parenting capacity assessment, formal recognition of shared/co-hadhanah with extended family, and state-supported parenting programs. Keywords: hadhanah; intellectual disability; tunagrahita; child custody; Islamic family law; maqasid al-shari'ah; child protection law; Indonesia